ANALISIS BIOMEKANIK KINETIK PADA ATLET BADMINTON DENGAN NYERI LUTUT SAAT GERAKAN BACKHAND DIAGONAL FORWARD LUNGES (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2022)
AbstractBadminton is a popular racquet sport around the world, this sport has the characteristics of explosive and intensive movements. The incidence of badminton injuries less than the other sports, but the severity is higher, one of the most common injuries is knee injury The purpose of this study was to see there was a relationship or not between the quality of knee pain (measured by KOOS), muscle activation (measured by surface EMG) and to determine whether there is an effect of multiregional history injury on the activation of m.vastus medialis oblique, m.vastus lateralis, m.biceps femoris and m.erector spine during backhand diagonal forward lunges. This type of research is a cross sectional study design The samples in this study were 21 athletes who were included in the inclusion criteria. The results of the normality test were by Shapiro Wilk the results obtained were p 0.064> 0.05, the correlation test using Pearson correalation 0.00 <00.5 there is a strong relationship between the quality of pain with muscle activation and different tests using the independent sample t-test m.erector spine (0.04 <0.05) showed an effect of multiregional injury history on activation on m.erector spine. Keywords: Badminton, Lunges, Knee Pain, Muscle activation